A Novel PhoP/PhoQ Regulation Pathway Modulates the Survival of Extraintestinal Pathogenic Escherichia coli in Macrophages - Zhuge, Xiangkai; Sun, Yu; Xue, Feng; Tang, Fang; Ren, Jianluan; Li, Dezhi; Wang, Juanfang; Jiang, Min; Dai, Jianjun (Frontiers in Immunology, 2018)
The extra-intestinal pathogenic E. coli (ExPEC) is a typical facultative intracellular bacterial pathogen. Sensing the environmental stimuli and undertaking adaptive change are crucial for ExPEC to successfully colonize in specific extraintestinal niches. The previous studies show that pathogens exploit two-component systems (TCSs) in response to the host environments during its infection. The PhoP/PhoQ is a typical TCS which is ubiquitous in gram-negative bacteria. However, there is an incompletely understanding about critical regulatory roles of PhoP/PhoQ in ExPEC pathogenesis. Conjugative ColV-related plasmids are responsible for ExPEC virulence, which is associated with ExPEC zoonotic risk. In this study, the molecular characteristics of HlyF, Mig-14 ortholog (Mig-14p), and OmpT variant (OmpTp) encoded by ColV plasmids were identified. Mig-14p and OmpTp played important roles in conferring ExPEC resistance to cationic antimicrobial peptides (CAMPs) during the infection. Moreover, HlyF and Mig-14p acted as intracellular survival factors to promote ExPEC resistance to macrophages killing. The hlyF and Mig-14p formed an operon in ExPEC ColV plasmid, and PhoP acted as a transcriptional activator of hlyF operon by directly binding to the PhlyF promoter. The acidic pH and CAMPs could additively stimulate ExPEC PhoQ/PhoP activities to up-regulate the expression of HlyF and Mig-14p. Our studies revealed that the novel PhoP/PhoQ-HlyF signaling pathway directly up-regulates the production of ExPEC outer membrane vesicles (OMVs). Furthermore, our study first clarified that this PhoP/PhoQ-HlyF pathway was essential for ExPEC intracellular survival in macrophages. It was required to prevent the fusion of ExPEC-containing phagosomes with lysosomes. Moreover, PhoP/PhoQ-HlyF pathway facilitated the inhibition of the phagolysosomal acidification and disruption of the phagolysosomal membranes. In addition, this pathway might promote the formation of ExPEC-containing autophagosome during ExPEC replication in macrophages. Collectively, our studies suggested that PhoP/PhoQ system and CloV plasmids could facilitate ExPEC survival and replication within macrophages.